COMUNICAÇÃO COMUNITÁRIA E DIREITO À MORADIA: A experiência de mobilização do movimento de moradia com a Rádio Z FM na Área do Chafik em Mauá-SP - Quintino, Raquel (2011)
Research on the conditions for the community media contribute to the participation and organization of popular movements. The objectives are to analyze the relations between community radio and housing rights and to understand the implications on the political communication development process sustained by a methodology of dialogical action in content production conducted by the agents of the housing movement. The dialectical approach is mainly based on the Paulo Freire´s thoughts. The research techniques are the literature review, the documentary and action-research developed together with the Association for Housing Development in Brazil - ADEHAB that acts in the region known as Chafiks area, in Jardim Zaíra, Maua, São Paulo, in partnership with the Community Radio Z FM, placed in the same locality. It is concluded that the creation of new community communication flows outputs on the strengthening of the popular movement and community radio and the main conditions for this process is the popular movements provisions to appropriate communicative areas for reinventing their practices.